PENGARUH MODERNISASI ADMINISTRASI PERPAJAKAN, TARIF, MORAL DAN NASIONALISME PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK PEKERJA BEBAS - Yustin Giftiani; Dwi Fionasari; Rama Gitasuci (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2025)
The purpose of this study is to examine the influence of tax administration modernization, tax rates, tax morale, and tax nationalism toward taxpayers’ compliance of freelance workers at the Pekanbaru Tampan Pratama Tax Service Office (KPP). This research adopts a quantitative approach through the application of a survey method. The data were obtained by distributing questionnaires to 100 freelance taxpayers registered at the Pekanbaru Tampan Pratama Tax Service Office and analyzed using Multiple linear regression analysis was employed, and the findings reveal that, partially, tax administration modernization, tax rates, tax morale, and tax nationalism each exert a positive and significant influence on taxpayer compliance. of freelance workers. This finding confirms that improving the administration system, implementing appropriate tax rates, moral awareness, and taxpayer nationalism are important factors in increasing tax compliance in the freelance worker group”